2003
DOI: 10.1002/mrd.10285
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous cytoplast and karyoplast transplantation reveals that the cytoplasm determines the developmental fate of the nucleus in mouse oocytes

Abstract: The relationship between nucleus and cytoplasm can be well revealed by nuclear transplantation. Here, we have investigated the behavior changes of the reconstructed oocytes after transferring the karyoplasts from mouse GV, MI, and MII oocytes into the cytoplasts at the different developmental stages. When the GV cytoplast was used as recipient and MI or MII karyoplast was used as donor (MI-GV pair and MII-GV pair), the reconstructed pairs extruded a polar body after electrofusion and culture. Both the cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Immunoblotting showed that mitogenactivated protein kinase (MAPK) activity was high in MI and MII cytoplasts but not detected in GV 4 cytoplast. The results demonstrated that the cytoplsmic environment determines the behavior of asynchronous donors [1].…”
Section: Introductionmentioning
confidence: 90%
“…Immunoblotting showed that mitogenactivated protein kinase (MAPK) activity was high in MI and MII cytoplasts but not detected in GV 4 cytoplast. The results demonstrated that the cytoplsmic environment determines the behavior of asynchronous donors [1].…”
Section: Introductionmentioning
confidence: 90%
“…ERK) and securin (a.k.a., pituitary tumor transforming gene 1, PTTG1) proteins was performed by western blotting as described (18). Briefly, oocytes were lysed in Laemmli lysis buffer (BioRad Laboratories, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Both oocytes, donor and recipient, must be in the same stage of maturation (Cheng et al, 2003a). This transfer can be basically performed at two stages of oocyte maturation, either between two metaphase I or between two metaphase II oocytes.…”
Section: Exchange Of Whole Chromosome Groupsmentioning
confidence: 99%